2008
DOI: 10.1016/j.electacta.2007.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical study of perchloroethylene reduction at copper electrodes in neutral aqueous medium

Abstract: Ag/AgCl/KCl(3M) carbon residues are the main product, detected on the copper surface by SERS (and confirmed by XPS), whereas in solution higher levels of dichloroethylene and trichloroethylene are detected with a DCE/TCE ratio bellow 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Perchloroethylene (PCE) is a widely used solvent in many areas of industry and has been reported as a major intermediate in the degradation of other chlorinated compounds. In our laboratory we are analyzing the degradation of this compound using different approaches: (i) by electrochemical treatments with not only fundamental [25,26] but also applied [27,28] studies; (ii) sonochemical treatments [29] and now (iii) sonoelectrochemical treatments, as in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Perchloroethylene (PCE) is a widely used solvent in many areas of industry and has been reported as a major intermediate in the degradation of other chlorinated compounds. In our laboratory we are analyzing the degradation of this compound using different approaches: (i) by electrochemical treatments with not only fundamental [25,26] but also applied [27,28] studies; (ii) sonochemical treatments [29] and now (iii) sonoelectrochemical treatments, as in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…are widely used as cathode materials. [26][27][28][29] Especially noble metals such as Pt and Pd have excellent catalytic property for electrochemical hydrodechlorination due to their low electric potential of producing hydrogen and high capacity of adsorbing hydrogen. [30][31][32] However, high cost actually limits the application of noble metals Pt and Pd.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some electrochemical methods have been proposed for the abatement and the detection [24] of these substances. The electrochemical abatement in water can be performed by the anodic oxidation to carbon dioxide, often called ''electrochemical incineration" [2][3][4][5] or the cathodic reduction to de-halogenated aliphatic hydrocarbons [6][7][8][9][10][11][12][13][14][15][16][17][18]. Furthermore, a third electrochemical route, based on the anodic oxidation to carbon dioxide coupled with the cathodic reduction to de-halogenated hydrocarbons, was proposed [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a certain attention has been devoted to the utilization of electrode materials characterized by electrocatalytic activity for the reduction of organic halides such as Pd, Pt, Ag, and Cu [6][7][8][9][10][11][12][13][14][15][16][17]. Sonoyama and Sakata showed that chloroform can be mainly converted in the corresponding alkane in water at Ag impregnated carbon fiber electrodes up to residual concentrations below 1 ppm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation